Rental strategy for energy storage to participate in frequency regulation market. Issue 1 (21st June 2022) - Wang, Xiaorong; Yu, Yundong; Yan, Xiaohe; Liu, Nian
Abstract: Energy storage (ES) can help the renewable energy sources to smooth their output and enhance their profits, which promotes the installation of ES. However, it is inappropriate for small‐scale renewable energy communities (REC) to invest costly ES, which requests a new business model to explore the possibility to rent ES for more returns. This paper proposes an ES rental strategy for REC to participate in the frequency regulation market (FRM). Firstly, the FRM is modelled considering the regulation capacity and mileage price. Then, the rental model for REC is built considering capacity rental costs and ES using costs. The correlation of rental capacity with reserved capacity and mileage is built through rental costs and revenue in FRM. The operation method for ES is carried out to maximise the total profits of REC. Finally, the whole model is demonstrated with a REC which has 35 MW photovoltaic and 113 MW wind turbine. The results show that under different rental and market prices, the REC can effectively choose the optimal rental strategy and its profits can mostly be raised by 19.63%.